1983
DOI: 10.1159/000137807
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide Hydrolase in Human Fetal Liver

Abstract: Epoxide hydrolase activity towards styrene oxide was measured in the microsomal fraction of 20 human fetal livers. The enzymatic activity was 5.60 ± 0.52 nmol/ min/mg (mean ± SE) which is about 40 % of the previously reported value in human adult liver microsomes. No relation between enzymatic activity and fetal age was observed. The kinetics of the enzyme were studied in 6 different livers and found to obey Michaelis-Menten kinetics. The Km ranged between 0.25 and 0.54 mmol/l and Vmax be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The sulfotransferase activity was not de pendent on the length of storage. The large interindividual variation seems to be typical of the sulfotransferase because our previous studies on acetyl transferase [Pacifici et al, 1986], glutathione transferase [Pacifici et al, 1981[Pacifici et al, , 1987, UDP-glucuronyl transferase [Pacifici et al, 1982] and microsomal epox ide hydrolase [Pacifici and Rane, 1983] have shown that the activity of these enzymes var ies in a more narrow range. The exposure of a fetus to molecules inactivated by the sulfo transferase may thus be difficult to predict in human fetus.…”
Section: Discussionmentioning
confidence: 95%
“…The sulfotransferase activity was not de pendent on the length of storage. The large interindividual variation seems to be typical of the sulfotransferase because our previous studies on acetyl transferase [Pacifici et al, 1986], glutathione transferase [Pacifici et al, 1981[Pacifici et al, , 1987, UDP-glucuronyl transferase [Pacifici et al, 1982] and microsomal epox ide hydrolase [Pacifici and Rane, 1983] have shown that the activity of these enzymes var ies in a more narrow range. The exposure of a fetus to molecules inactivated by the sulfo transferase may thus be difficult to predict in human fetus.…”
Section: Discussionmentioning
confidence: 95%
“…Different forms of EH have been dem onstrated in microsomes from human adult liver [Guengerich et al, 1979a] and it is pos sible that our findings reflect the presence of different isozymes. The existence of multiple forms of EH in human fetal liver has pre viously been suggested [Pacifici and Rane, 1983a].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that these two enzymatic pathways are operating in the mid-gesta tional human fetus [Pacifici andRane, 1982, 1983a;Pacifici et al. 1981Pacifici et al. , 1983a.…”
Section: Introductionmentioning
confidence: 99%
“…In fetal liver, adrenal, kidney, and lung ranging from 16 to 25 weeks gestation, EPHX1 activity, as measured using the substrate benzo[a]pyrene-4,5-oxide, was reported as 150 pmol/min/mg protein in the liver and adrenal glands, but only 50 pmol/min/mg protein in kidney and lung (Pacifici et al, 1983b). This same group subsequently demonstrated an increase in hepatic EPHX1 catalytic activity between 10 and 25 weeks gestation, although sample-size and intersubject variability prevented the authors from suggesting anything other than a weak correlation between activity and gestational age (Pacifici and Rane, 1983). Employing an immunological approach in eight fetal livers ranging from 17 to 27 weeks gestation, Cresteil et al (1985) demonstrated EPHX1-specific content between approximately 40 and 400 pmol/mg microsomal protein whereas in four adult liver samples, the specific content ranged from 750 to 1200 pmol/mg microsomal protein.…”
Section: Epoxide Hydrolasementioning
confidence: 98%